Empiricism and governance: Revisiting Hume's contributions to political philosophy and human nature - Gongqing, Li; Sabjan, Muhammad Azizan; Mohamad, Nur Izzaty (International Journal of Asian Social Science, 2025)
This study examines David Hume’s political philosophy, focusing on his empiricist approach to governance, human nature, and justice. It highlights how Hume’s ideas remain relevant to contemporary issues such as institutional trust, legitimacy, and governance challenges. A qualitative narrative literature review was conducted using primary sources (Hume’s A Treatise of Human Nature, Essays, Moral, Political, and Literary) and secondary literature. A thematic analysis identified key patterns in Hume’s political thought. Hume’s empiricism provides a pragmatic governance approach, emphasizing observation-based knowledge, skepticism of absolute authority, and adaptability. His conception of human nature, rooted in passions, customs, and social cooperation, offers insights into political legitimacy and social cohesion. His view of justice as a social construct remains applicable to modern governance and inequality debates. Hume’s empiricist framework supports evidence-based governance, emphasizing adaptive political institutions. His insights help address challenges in political legitimacy and public trust. This study underscores the relevance of Hume’s political philosophy in shaping contemporary governance, particularly in addressing institutional trust and justice.